Radionuclides in sediment cores of the Atlantic sector of the Southern Ocean, supplementary data to: Frank, Martin; Gersonde, Rainer; Rutgers van der Loeff, Michiel M; Bohrmann, Gerhard; Nürnberg, Christine Caroline; Kubik, Peter W; Suter, Martin; Mangini, Augusto (2000): Similar glacial and interglacial export bioproductivity in the Atlantic sector of the Southern Ocean: multiproxy evidence and implications for atmospheric CO2. Paleoceanography, 15(6), 642-658 - Frank, Martin; Gersonde, Rainer; Rutgers van der Loeff, Michiel M (PANGAEA - Data Publisher for Earth & Environmental Science, 2000)
We present time series of export productivity proxy data including 230Thex-normalized deposition rates (rain rates) of 10Be, dissolution-corrected biogenic Ba, and biogenic opal as well as authigenic U concentrations which are complemented by rain rates of total (detrital) Fe and sea ice indicating diatom abundances from five sediment cores across the Atlantic sector of the Southern Ocean covering the past 150,000 years. The results suggest that 10Be rain rates and authigenic U concentration cannot serve as quantitative paleoproductivity proxies because they have also been influenced by detrital particle fluxes in the case of 10Be and bulk sedimentation rates (sediment focussing) and deep water oxygenation in the case of U. The combined results of the remaining productivity proxies of this study (rain rates of biogenic opal and biogenic Ba in those sections without authigenic U) and other previously published proxy data from the Southern Ocean (231Pa/230Th and nitrogen isotopes) suggest that a combination of sea ice cover, shallow remineralization depth, and stratification of the glacial water column south of the present position of the Antarctic Polar Front and possibly Fe fertilization north of it have been the main controlling factors of export paleoproductivity in the Southern Ocean over the last 150,000 years. An overall glacial increase of export paleoproductivity is not supported by the data, implying that bioproductivity variations in the Southern Ocean are unlikely to have contributed to the major glacial atmospheric CO2 drawdown observed in ice cores.
This dataset is supplement to doi:10.1029/2000PA000497
Keywords: Datensammlung